Linitis Plastica of The Stomach: A Review - Rahman, Md Mizanur (Journal of Surgical Sciences, 2020)
Linitis plastica (LP) is a particular subtype of diffuse gastric cancer and is thought to have a separate entity in respect with its biological behaviour, pathology, presentation and treatment outcome. The poor prognosis of LP gastric cancer is due primarily to its advanced stage at diagnosis. The characteristic histopathological feature of this entity is cellular spread to the submucosa and stroma with minimal mucosal alterations accompanied by an excessive desmoplastic reaction. Despite recent research on alternative therapies, surgical resection appears the only potentially curative approach. Patient selection and multidisciplinary management are paramount when considering surgical resection in patients with gastric LP. The operative approach in patients with LP has historically been questioned because of the poor outcomes. The aim of this review is to highlight different dimension of linitis plastica stomach in respect to its definition, classification, clinico-pathological characters, diagnostic approaches and treatment outcome. Journal of Surgical Sciences (2018) Vol. 22 (2) : 125-138